Analysis of the Teacher's Role in Evaluation of Student Learning Performance Using the TOPSIS Model (Case Study of Smk Negeri 1 Lhokseumawe) - arief rahman; Zahratul Fitri; Zulkifli Zulkifli; Mutammimul Ula; Bambang Suhendra (Universitas Medan Area, 2022)
Analysis Teacher performance assessment is very decisive in the quality of teaching and learning, This has an effect at the high-satisfactory of college students in information the fabric provided. The problem at the time of the study was that the teacher's performance assessment did not involve students, both assessments were carried out manually by filling out the teacher's learning performance satisfaction form. Therefore, the need for a model in the assessment and the results obtained are not subjective. The development in this study applies the topsis model where the results of this model can provide recommendations for school principals in Teacher Performance Assessment. The application of this topsis model provides a solution/policy in teacher assessment by students which is seen from the ranking results in the form of superior, very good, good and unsatisfactory in the success of providing material. The purpose of this study is to facilitate, supervise, control and see the assessment of the learning performance of SMK Negeri 1 Lhokseumawe teachers in the analysis of information technology-based teacher assessment with a desktop-based topsis model. The results showed that the first rank with a value of 0.616 lia amalia, the second rank with a value of 0.614 and the third rank with a value of 0.605 on behalf of Nazaruddin. The consequences of this test are obtained from the assessment of the topsis version of the trainer's performance.